Investigation of the Mechanism of Siweixizangmaoru Decoction in Improving CIA-Induced Arthritis in Rats Based on Network Pharmacology and Experimental Verification - Niu, Yanfei; Yuan, Yanxiang; Wang, Tong; Yuan, Ruiying; Zhang, Min; Wang, Sicen; Tsering, Dikye; Huang, Shan; Li, Bin (Combinatorial Chemistry & High Throughput Screening, 2025)
BackgroundRheumatoid Arthritis (RA) is a chronic autoimmune disease with a complex etiology. Siweixizangmaoru Decoction (SXD) has been used to treat RA in Tibet for a long history as a classic Tibetan medicine formula. However, the potential pharmacological mechanism has not been elucidated yet.AimsThe aim of this study was to evaluate the efficacy and mechanism of action of SXD in the treatment of RA using network pharmacology and molecular docking analysis.MethodsNetwork pharmacology was employed to identify the potential bioactive components and key targets of SXD for the treatment of RA. Molecular docking of key targets and potential compounds was conducted. High-performance liquid chromatography was performed to validate the predicted active components of SXD. We established a rat model of RA and evaluated the histopathology of each group of rats. In addition, the levels of inflammatory factors in serum and the expression levels of PI3K/AKT and MAPK pathway-related proteins in synovial tissue were detected.ResultsThe results of network pharmacological analyses indicated that apigenin, rhamnolipids, kaempferol, quercetin, and naringenin are potential bioactive components of SXD for the treatment of rheumatoid arthritis and that their therapeutic effects may be related to the PI3K-Akt and MAPK pathways. The results of in vivo experiments show that SXD improved the arthritis index, significantly reduced joint swelling, and improved synovial inflammation and cartilage destruction.ConclusionNetwork pharmacology, along with experimental validation, provided a useful approach for understanding the pharmacological mechanism of Siweixizangmaoru decoction in RA.
Keywords: tibetan medicine formula